Anatomical variations of the tibialis anterior tendon insertion: An updated and comprehensive review - Zielinska, Nicol; Tubbs, Richard Shane; Paulsen, Friedrich; Szewczyk, Bartłomiej; Podgórski, Michał; Borowski, Andrzej; Olewnik, Łukasz (Journal of Clinical Medicine, 2021)
The tibialis anterior muscle originates on the lateral condyle of the tibia, on the upper two-thirds of the lateral surface of this bone, on the anterior surface of the interosseous membrane and on the deep surface of the fascia cruris. The distal attachment is typically at the medial cuneiform and first metatarsal. However, the tibialis anterior tendon can vary morphologically in both adults and fetuses. Different authors have created new classification systems for it. The main aim of this review is to present condensed information about the tibialis anterior tendon based on the available literature. Another aim is to compare classification systems and the results of previous studies.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Diagnosis; Fetuses; New classification; Systematic review; Tendon rupture; Tibialis anterior muscle